Homocysteine, pituitary and thyroid hormones in children with different physical growth levels after forest fires in the Chernobyl exclusion zone - Bandazhevskyi, Yu. I.; Dubova, N. F. (Environment & Health, 2022)
Objective We performed a comparative assessment of the blood levels of homocysteine, pituitary and thyroid hormones in children with different levels of physical development before and after forest fires in the Chornobyl exclusion zone (ChEZ) in 2015. Methods: We used immunochemical, instrumental, mathematical and statistical methods. Results: The analysis of variable dynamics was performed in 336 adolescents of the Polisskyi and the Ivankivskyi districts of Kyiv region. An association was found between homocysteine (Нсу), hormones of the pituitary-thyroid axis and physical development of children. A statistically significantly higher level of Нсу was observed in the adolescents from the Ivankivskyi district in comparison with the children from the Polisskyi district. Forest fires in the spring and summer of 2015 in the ChEZ should be considered the main cause for the increase in Нсу in the blood of the adolescents. The increased level of Т3 in the peripheral tissues induced by Нсy and TSH contributed to a decrease in the physical development index values. Due to a decrease in the intensity of the Т4 deiodination process, the insufficient formation of Т3 in the peripheral tissues was recorded in the group of children with a disharmonious high physical development.